Pengaruh Persepsi Harga, Kepercayaan Pengguna, Orientasi Merek, Dan Orientasi Belanja Terhadap Niat Beli Pada Bisnis E-Commerce (Studi Kasus Pada Mahasiswa Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta) - Sakti, Aji Seno Putro, Drs. Suyatmin Waskito Adi, M.Si (2017)
This study aims to to analyze the influence of price perception, trust by users, brand orientation, and shopping orientation to buy expenditure intention on business e-commerce done at the Faculty Economic and Business Muhammadiyah University of Surakarta. E-commerce own business in Indonesia up to development about 8.8 percent every year. Sample used in this research is a student accounting school of economics and business Muhammadiyah University of Surakarta respondents were 90, after passing Formula Slovin and reducing samples were not included criteria five respondens. In this study, hypothesis tested by using multiple regression. The research results show that trust by users, brand orientation and shopping orientation expenditure impact on intention buy on business e-commerce, while price perception has not been affecting the intention buy on business e-commerce because most people were affected the higher of the prices offered as long as can have goods that they wants.